More Urban Myths About Learning and Education: Challenging Eduquacks, Extraordinary Claims, and Alternative Facts - De Bruyckere, Pedro; Kirschner, Paul Arthur; Hulshof, Casper (New York: Routledge, 2020)
More Urban Myths About Learning and Education: Challenging Eduquacks, Extraordinary Claims, and Alternative Facts examines common beliefs about education and learning that are not supported by scientific evidence before using research to reveal the truth about each topic. The book comprises sections on educational approaches, curriculum, educational psychology, and educational policy, concluding with a critical look at evidence-based education itself. Does playing chess improve intelligence? Should tablets and keyboards replace handwriting? Is there any truth to the 10,000-hour rule for expertise? In an emerging, conversational style, authors Pedro de Bruyckere, Paul A. Kirschner, and Casper D. Hulshof tackle a set of pervasive myths, effectively separating fact from fiction in learning and education--back cover.
1. Myths about the 'what' -- 2. Myths about the 'how' -- 3. Myths about (educational) psychology -- 4. Myths about educational policy -- 5. Evidence-based education as an educational myth.
Includes bibliographical references (pages 159-188) and index.
Keywords: Education; Education and State; Education -- Philosophy